2021
DOI: 10.1111/eth.13207
|View full text |Cite
|
Sign up to set email alerts
|

Through a glass darkly? Divergent reactions of eight Lake Tanganyika cichlid species towards their mirror image in their natural environment

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…However, there are some artificialities in the mirror test, as the image does not respond to the fighting individual, therefore generating criticism of this method. Despite this criticism addressed to the mirror test, it was recently shown that several cichlid species under natural environments react to their mirror image with meaningful biological behaviors, according to the aggressive behavioral pattern of the species, regardless of any artificiality of the method 66 . Moreover, the aggressive behavior in the mirror test was found in several studies to positively correlate with the aggressiveness level of fish in live agonistic trials 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some artificialities in the mirror test, as the image does not respond to the fighting individual, therefore generating criticism of this method. Despite this criticism addressed to the mirror test, it was recently shown that several cichlid species under natural environments react to their mirror image with meaningful biological behaviors, according to the aggressive behavioral pattern of the species, regardless of any artificiality of the method 66 . Moreover, the aggressive behavior in the mirror test was found in several studies to positively correlate with the aggressiveness level of fish in live agonistic trials 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mirror-elicited aggression is a predictor of individual stress 70 and is associated with gene expression in the hypothalamus of critical genes involved in the stress response of Nile tilapia 71 . Furthermore, despite criticism addressed to this method, it was recently demonstrated that several cichlid species in their natural environments aggressively react to their mirror image, expressing resembling behavioral patterns presented during fights with co-specifics 66 .…”
Section: Methodsmentioning
confidence: 99%
“…The mark test (Gallup 1970), which purports to establish self-awareness, has biased mirror reactions in an anthropocentric way, thus distracting attention from what other reactions might indicate (Broom 2010;de Waal 2019). Many animals appear to see a conspecific in the mirror (Kusayama et al 2000), including fish, who tend to react aggressively (Josi & Frommen 2021) and others perform self directed actions in front of it (Broom 2014;Ari & D'Agostino 2016).…”
Section: Novel Objectsmentioning
confidence: 99%
“…Cichlid fishes make up about 10% of all teleost fish species. They are a diverse family of fish well known for being aggressive and territorial (Arnott and Elwood, 2009; Genner, Turner and Hawkins, 1999; Hirschenhauser et al, 2004; Josi and Frommen, 2021). Haplochromine cichlids are popular models in the study of adaptive radiation and speciation (Genner and Turner, 2005; Kocher, 2004; Moser et al, 2018; Seehausen and van Alphen, 1999).…”
Section: Introductionmentioning
confidence: 99%